Perancangan Basis Data dalam Sistem Informasi Manajemen Pendidikan Islam - Siti Nur Syafaah; Dina Hermina (Jurnal Riset Multidisiplin Edukasi, 2026)
Databases play a crucial role in supporting the management of student data, educators, curriculum, finance, and educational evaluation in a structured and integrated manner. However, in practice, Islamic educational institutions still face several challenges, including limited digital literacy among human resources, suboptimal data management, and resistance to technological change. This discussion highlights that database management is not only related to technical aspects but is also strongly influenced by the quality of Islamic educational management, which includes planning, organizing, actuating, and controlling. Therefore, strong managerial roles, effective leadership, and continuous support are required to optimize the use of information systems and databases in improving the quality of management and Islamic education.